A study on analysis of performance appraisal at imind technologies - BABU, MR. RAM; MS. SREEMATHI (The journal of contemporary issues in business and government, 2020)
The research paper titled Performance Appraisal : A study on analysis of performance appraisal at IMIND Technologies. The objective of the study is to find out various performance appraisal techniques followed and to know the awareness of performance appraisal system,analyse the performance appraisal system practiced in IMind Technologies ,to know the employees opinion regarding Performance Appraisal system practiced IMind Technologies, and also to know the important factors influencing the employees in Performance System. Exploratory research and causal research is used in the study and the sample size of the study is 86.The tools used in the study are mean analysis, frequency analysis, Independent sample T test and ANOVA. It is found that the performance appraisal system is followed in the organization but it is not outstanding and Also clear that employees are satisfied with the content of the appraisal system in the relation to their job but the performance appraisal system in organization does not help them in identifying their potential for growth and also employees accept that purpose of performance appraisal practiced is for promotional rewards and for training but here in the organization where the respondents don’t get both monetary and promotional reward.